Predictors of inflammatory lower airway disease in cats presented to the emergency room in respiratory distress: a case-control study. Issue 12 (December 2021) - Chalifoux, Nolan V; Drobatz, Kenneth J; Reineke, Erica L
Objectives: The objective of the study was to identify whether venous blood gas (VBG) variables may serve as a predictor of inflammatory lower airway disease (ILAD) in cats presenting with respiratory distress. A secondary objective of this study was to compare the diagnostic utility of patient signalment, history and physical examination findings, as compared with VBG variables. Methods: The medical records of cats presenting with respiratory distress secondary to ILAD (54 cases) and non-ILAD (121 controls) were retrospectively reviewed. Results: No admission VBG variables were predictive of a final diagnosis of ILAD. Comparatively, multivariable analysis identified a history of a cough ( P <0.001), increased respiratory rate ( P  = 0.001), the presence of an abdominal component to respiration ( P  = 0.007) and the absence of pleural effusion ( P <0.01) to be independently associated with a final diagnosis of ILAD. Cats with a history of a cough and an abdominal component to respiration had 7.86 and 5.81 greater odds of being diagnosed with ILAD, respectively. Cats with pleural effusion had 7.43 lower odds of having this final diagnosis. For every 10 breaths/min increase in respiratory rate, cats had 1.48 greater odds of being diagnosed with ILAD. Cats diagnosed with ILAD had a survival rate of 94% (95% CI 84–99%) vs 61% (95% CI 51–70%) for non-ILAD controls ( P <0.001). Conclusions and relevance: The results of this study found patient history and physical examination findings to be more useful predictors of a final diagnosis of ILAD in comparison with VBG variables at presentation. A history of a cough, an abdominal component to respiration and a lack of pleural effusion were found to be significant predictors of this diagnosis. Further investigation into the role of respiratory rate in ILAD is warranted.